Transformative Patterns in Modern Family Structures and Their Influence on Contemporary Social Cohesion - Nur Özkaya, Zeynep (Journal of Social Science Studies, 2022)
This study explores how structural and functional changes in modern family life shape social interaction and cohesion within contemporary society. Utilizing a literature-based analytical approach, the research investigates emerging patterns in family composition, such as delayed marriages, blended households, and shifting parental roles, alongside evolving functions such as caregiving, authority, and value transmission. Drawing from a wide range of sociological, psychological, and legal scholarship, the analysis reveals that transformations in the modern family are both reflective of and contributory to broader socio-cultural transitions. These changes influence not only interpersonal dynamics within households but also extend to civic participation, intergenerational solidarity, and the capacity for social trust. Although some adaptations have led to challenges—such as reduced communication or fragmented relational expectations—others suggest emerging possibilities for reimagining intimacy, responsibility, and support within decentralized networks. The findings suggest that modern families, despite structural variability, retain a foundational capacity to generate social cohesion when intentionality, empathy, and interconnectivity are actively cultivated. By embracing the multiplicity of family forms and functions, society can better align social institutions to support the evolving needs and contributions of contemporary family life.